Human Body Affected by Mobile Phone and Electromagnetic Field Radiation - Duranková, Silvia; Kalavsky, Richard (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2024)
Humans have been surrounded by various forms of radiation since creation. The first type of radiation is electromagnetic in nature. Radioactive radiation partly emanates from the earth surface. Nowadays, each of us uses a mobile phone daily. Computers, monitors, and televisions have added seriousness to this issue, as they generate both electrostatic and electromagnetic fields. Electromagnetic radiation can cause everything from insomnia to serious health problems that threaten people lives. It is this study that is intended to bring the issue of the occurrence and localization of such zones into focus. Such electromagnetic radiation, invisible to humans, is faced by a large part of the population. It is dangerous to stay in these locations for a long time. People who sleep in this zone for long periods of time are the most vulnerable. In our study, we also looked at the impact of the use of mobile phones and other devices that generate electromagnetic fields. In this study, our aim was to provide a theoretical overview of this issue, which has not received much attention, and which can be a trigger for many health diseases, especially in combination with geopathogenic zones.